2014
DOI: 10.1063/1.4896961
|View full text |Cite
|
Sign up to set email alerts
|

Role of W and Mn for reliable 1X nanometer-node ultra-large-scale integration Cu interconnects proved by atom probe tomography

Abstract: Experimental characterization and modeling of the reliability of three-terminal dual-damascene Cu interconnect trees

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…We previously evaluated alloy films of Co with W addition [Co(W)] formed by CVD or ALD as an alternative material to the PVD-Ta/TaN double layer, [30][31][32] because Co(W) is thought to have low resistivity and good adhesion with Cu regardless of possible impurities in the interface between Co(W) and Cu derived from ligands or byproducts of precursors. [33][34][35][36][37] In this current study, we successfully designed oxygen-free Co(W) films by thermal CVD or ALD using NH 3 and two oxygen-free precursors, namely, bis (N-tert-butyl-N -ethyl-propaneamidinato) cobalt (II) [Co(AMD) 2 ] and bis (tert-butylimino) bis (dimethylamino) tungsten (IV) (BTBMW), whose molecular structures are shown in Fig. 1.…”
mentioning
confidence: 99%
“…We previously evaluated alloy films of Co with W addition [Co(W)] formed by CVD or ALD as an alternative material to the PVD-Ta/TaN double layer, [30][31][32] because Co(W) is thought to have low resistivity and good adhesion with Cu regardless of possible impurities in the interface between Co(W) and Cu derived from ligands or byproducts of precursors. [33][34][35][36][37] In this current study, we successfully designed oxygen-free Co(W) films by thermal CVD or ALD using NH 3 and two oxygen-free precursors, namely, bis (N-tert-butyl-N -ethyl-propaneamidinato) cobalt (II) [Co(AMD) 2 ] and bis (tert-butylimino) bis (dimethylamino) tungsten (IV) (BTBMW), whose molecular structures are shown in Fig. 1.…”
mentioning
confidence: 99%
“…We recently observed the encapsulated structure by three-dimensional atom probe tomography method. 51 This clearly showed that stuffed grain boundaries efficiently prevented Cu diffusion. In addition, some intrinsic pin-holes in nano-meter-thick CVD/ALD-Co(W) lms could be stuffed by Mn addition in Cu seed layer for the actual application.…”
Section: Barrier Performance Against Cu Diffusionmentioning
confidence: 93%
“…135,136 This nullified the benefits of capacitance scaling by implementing increasingly difficult to integrate highly porous extreme low-k ILD materials. 102 Further, efforts to downscale the thickness of the TNT barrier [136][137][138][139] or adopt alternate metallization materials [140][141][142][143][144][145] to mitigate the resistivity impact were only exacerbated by the use of highly porous ILD materials. Similarly, continued delays in the availability of EUV lithography [146][147][148] forced the adoption of intricate pitch division/multi-patterning techniques 149,150 that multiplied the patterning induced damage and increase in k value for porous ILDs.…”
Section: The End Of Permittivity Scaling?mentioning
confidence: 99%